Choujin X. Volume 10 - Ishida, Sui (Viz signature., 2025)
"Dark humor and quirky horror unite in this tale of clashing heroes and monsters from the creator of Tokyo Ghoul and Tokyo Ghoul: re! Best friends Tokio and Azuma do everything together, even if most of the time it feels like Tokio is just stumbling along in Azuma's cooler, more talented footsteps. But when they're attacked one night by a superhuman mutant called a choujin, Tokio finally has a chance to shine-by turning into a choujin himself! After years of clashing with Zora and her forces, Yamato Mori now has a chance to defeat their former leader. But this final showdown will be on Zora's home turf, and everyone knows the cost of storming her tower will be high. Will the battle be the perfect chance for Tokio and his friends to prove themselves to their mentors, or is this finally the fight they won't walk away from?" --